Entrepreneurial Marketing and Quality Performance of Small-Scale Business in Ikeja, Lagos State, Nigeria - Dosunmu, Margaret Moronke; Bukki, Abolaji Olugbenga (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
SMEs are socially and economically important as they are a source of employment and contribute to the national development of any nation or country. This study investigated SMEs’ entrepreneurial marketing and quality performance in Ikeja, Lagos State. The work sought to determine the nature of entrepreneurial marketing among SME owners, examine the level of SMEs’ quality performance, and investigate the relationship among proactiveness, innovativeness, risk-taking and SMEs performance. The study employed a descriptive research design, and two hundred and fifty-six (256) SME owners were selected from different areas in Ikeja using a simple random sampling technique. Primary data were collected through two standardized scales, and the statistical tools of frequency count, percentages, mean, standard deviation, regression and ANOVA were used to analyze the data. The result showed that SME owners had very high entrepreneurial marketing skills in Ikeja, Lagos State. The quality performance among the SMEs included a system approach to management, continual improvement, a factual approach to decision-making, and mutually beneficial customer relationships, which were the different levels of quality performance among SMEs in Ikeja, Lagos State. There was also a significant relationship between quality performance, proactiveness, innovativeness and risk-taking. However, proactiveness had a substantial relationship with innovativeness and risk-taking. Meanwhile, risk-taking had an important relationship with innovativeness, and there was a significant composite influence of proactiveness, innovativeness and risk-taking on the quality performance of the SMEs. The study recommended that SME owners improve their innovativeness to increase their sustainability and profitability.